Immature Sword Bean (Canavalia gladiata) Pod Alleviates Allergic Rhinitis (A Double-Blind Trial) Through PI3K/Akt/mTOR Signaling - Hwang, Hye-Jeong; Yoon, Hyeock; Cho, Joo-Hyung; Lee, Seong; Hwang, Kyung-A; Kim, Young Jun (Nutrients, 2025)
Background: Allergic rhinitis is an IgE-mediated condition of nasal congestion, runny nose, and sneezing which significantly impairs the quality of life. Current treatments, including antihistamines, often have long-term side effects, leading patients to seek safer alternatives. Objectives: Therefore, in this study, we aimed to evaluate the symptom relief efficacy of immature sword bean pod (SBP) extract, a natural material, in patients with allergic rhinitis, explore the mechanisms by which SBP regulates allergic immune responses, and evaluate its efficacy and safety as a functional ingredient in the management of allergic rhinitis. Methods: In a double-blind, placebo-controlled, randomized trial involving 64 participants with perennial allergic rhinitis, the subjects were assigned to receive either SBP or placebo orally for six weeks. Results: The SBP group exhibited significant improvements in nasal congestion (interaction p = 0.031), RQLQ (interaction p = 0.001), sleep (interaction p = 0.004), systemic reaction (interaction p = 0.002), daily life (interaction p = 0.047), and nasal symptoms (interaction p = 0.002). SBP treatment in EoL-1 and HMC-1 cells also led to a notable reduction in eosinophil cationic protein levels (p < 0.05), a key biomarker of allergic inflammation, by inhibiting PI3K/Akt/mTOR activation, resulting in decreased eosinophil activity. Conclusions: These findings suggest that the SBP extract is a promising natural treatment for allergic rhinitis, offering both efficacy and safety by improving key symptoms and reducing inflammatory responses.